2006
DOI: 10.1002/bdra.20313
|View full text |Cite
|
Sign up to set email alerts
|

Potential association between infertility and spinal neural tube defects in offspring

Abstract: Background-To examine the possible association between infertility and spinal neural tube defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
0
23
3
Order By: Relevance
“…Their data suggest that there might be a slight and probable indirect association between the use of CC and NTD. Recently, Wu et al (12) found an OR of 11.7 (95% CI 2.0-44.8) for NTD with the use of CC within the window spanning 60 days before to 15 days after conception. The number of CC cycles in the 12 months before conception was higher in mothers with infants with NTDs than in control mothers (mean 5.7 vs. 2.6 cycles, P¼.01).…”
Section: Clomiphene Citratementioning
confidence: 97%
“…Their data suggest that there might be a slight and probable indirect association between the use of CC and NTD. Recently, Wu et al (12) found an OR of 11.7 (95% CI 2.0-44.8) for NTD with the use of CC within the window spanning 60 days before to 15 days after conception. The number of CC cycles in the 12 months before conception was higher in mothers with infants with NTDs than in control mothers (mean 5.7 vs. 2.6 cycles, P¼.01).…”
Section: Clomiphene Citratementioning
confidence: 97%
“…Across cohort and case-control studies there is no evidence that exposure to clomiphene citrate (G03GB02) in the periconceptional period increases the rate of all CAs combined. There is conflicting evidence of an association with NTDs [135][136][137]. Clomiphene has been associated with coarctation of the aorta [66,138], anencephaly, Dandy Walker malformation, septal heart defects, muscular ventricular septal defects, esophageal atresia, cloacal exstrophy, craniosynostosis and omphalocele but multiple comparisons and small numbers of cases make these findings tentative [66].…”
Section: G03gbmentioning
confidence: 99%
“…Since then, additional case–control and cohort studies have found controversial results. In particular, in 2006, a case–control study conducted in the Kaiser permanent claims database found an association between CC exposure in pregnancy and an increased risk of NTDs …”
Section: Introductionmentioning
confidence: 99%
“…In particular, in 2006, a case-control study conducted in the Kaiser permanent claims database found an association between CC exposure in pregnancy and an increased risk of NTDs. 6 The aim of this study is to provide an up-to-date metaanalysis evaluating the association between periconceptional CC exposure and the risk of NTDs.…”
Section: Introductionmentioning
confidence: 99%